Saving Face - Wu, Alice; Essandoh, Ato.; Guang Lan Koh; Jessica Hecht; Jin Wang; Joan Chen; Lynn Chen; Michelle Krusiec (USA Sony Pictures, 2004)
A Chinese-American surgeon, living in Manhattan, is shocked when her single mother shows up on her doorstep pregnant. To help her mom save face and avoid the taboo in the Chinese community of an unmarried woman pregnant, the doctor helps her mom find Mr. Right. Cultures clash in this film that explores culture shock.
A Chinese-American lesbian and her traditionalist mother are reluctant to go public with secret loves that clash against cultural expectations.
Alice Wu
Languages: English, Italian Subtitles: Czech, English, Hungarian, Polish, Russian, Turkish, Italian, Dutch, Arabic, Bulgarian, Serbo-Croatian, Danish, Finnish, Greek, Hebrew, Hindi, Norwegian, Romanian, Slovenian, Swedish
Keywords: Drama; Romance; Comedy